2012
DOI: 10.1039/c1dt11133g
|View full text |Cite
|
Sign up to set email alerts
|

Can a meso-type dinuclear complex be chiral?: dinuclear β-diketonato Ru(III) complexes

Abstract: Dinuclear Ru(III) complexes, [Ru(III)(acac)(2)(dabe)Ru(III)(acac)(2)] (acacH = acetylacetone; dabeH(2) = 1, 2-diacetyl-1,2-dibenzoylethane) and [Ru(III)(acac)(2)(tbet)Ru(III)(acac)(2)] (tbetH(2) = 1,1,2,2-tetrabenzoylethane) were synthesized by reacting [Ru(acac)(2)(CH(3)CN)(2)]PF(6) with dabeH(2) and tbetH(2) respectively, in toluene. The X-ray structural analysis of a meso-type dinuclear Ru(III) complex, ΔΛ-[Ru(III)(acac)(2)(dabe)Ru(III)(acac)(2)], showed that the bridging part became chiral due to the ortho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…In this context, Sato et al investigated in detail the VCD spectra of tris (acetyl acetonate) complexes with different transition metal ions, 18 of their mixed ligand complexes, 19,20 and of larger multi-core complexes. [21][22][23] Recently, we carried out a systematic study on the VCD spectra of transition metal complexes of copper(II) and nickel(II) with the chiral diamine ligands, trans-1,2-diamino cyclohexane (chxn). 24 It was shown that the obtained VCD spectra feature characteristic differences between the tris-complexes of Ni (II) and Cu(II), and between the tris-and bis-complexes of Cu(II).…”
Section: Introductionmentioning
confidence: 99%
“…In this context, Sato et al investigated in detail the VCD spectra of tris (acetyl acetonate) complexes with different transition metal ions, 18 of their mixed ligand complexes, 19,20 and of larger multi-core complexes. [21][22][23] Recently, we carried out a systematic study on the VCD spectra of transition metal complexes of copper(II) and nickel(II) with the chiral diamine ligands, trans-1,2-diamino cyclohexane (chxn). 24 It was shown that the obtained VCD spectra feature characteristic differences between the tris-complexes of Ni (II) and Cu(II), and between the tris-and bis-complexes of Cu(II).…”
Section: Introductionmentioning
confidence: 99%
“…Heterometallic oligomers were prepared by connecting bis(β-diketonato)ruthenium(III) moieties to a labile metal ion through bis-β-diketonato bridging ligands [19,21,22,52,53]. The main attention is focused on the possibility of the induction of chiral coordination structures around the labile metal ion.…”
Section: Vcd Application To Oligomers Of Chiral Metal Complexes Inmentioning
confidence: 99%
“…In this section, we report the chiral induction of a bridging part by use of an non-symmetrical β-diketonato ligand, in which the twisting of two β-diketonato planes causes C 2 symmetry [21,24]. …”
Section: Vcd Application To Oligomers Of Chiral Metal Complexes Inmentioning
confidence: 99%
See 2 more Smart Citations